A structural model of creative industry for small medium enterprise innovation indexes - Zafriana, L; Nasution, A H (Institut Teknologi Sepuluh Nopember, 2018)
Problems on Indonesia Small-Medium Enterprise (SME) are identified in the financial area, organization and management, network and export capabilities. There are numerous cases suggesting that SME problem lies in the competitiveness area, related with their innovation capabilities. Reducing its weakness, it is needed to build SME innovation indexes by using Structural Equation Modelling (SEM). This model is composed of 4 (four) construct variables, its technology, marketing/information, product quality, and organization management. All of variables will compose values of sub indexes dan efficiency market that determine the final value of SME innovation indexes in different criteria. The application of structural model on SME innovation indexes by using simulation data conclude that technology and marketing/information variables have impact on strategy sub indexes as 5,3%. Quality product and management/organization variables have impact as 149,8% on market efficiency. By using normalization value, the biggest role as 96% is determined by product quality and management organization, the rest of 4% come from technology and market/information. Sub indexes variable and market efficiency have impact on SME Innovation Indexes as 49,4%.